Tasks of the Drafter of Legislation in Forming Regional Regulations (Study of the Implementation of Government Regulation Number 59 of 2015) - Ahmad Luthfi (Indonesian State Law Review, 2019)
The formation of regional regulations can involve drafters of laws and regulations in accordance with Article 98 of Law number 12 of 2011 concerning Formation of Legislation and strengthened by Government Regulation number 59 of 2015 concerning Participation of Drafters of Legislation in Forming Legislation and the builder. This study aims to describe the tasks of drafting laws and regulations in the formation of regional regulations and the influence of drafters of statutory regulations at the Regional Office of the Ministry of Law and Human Rights in Central Java on the formation of quality regional regulations. The research method uses qualitative research and an empirical juridical approach. Primary data obtained from interviews and observations, secondary data obtained from documents and photographs. The results of this study indicate that the Drafter of Legislation can follow every stage of the process of forming regional regulations in accordance with the mandate of the applicable law and is further confirmed through a cooperation agreement between the authorized agencies. The participation of Drafters of Legislation in the formation of regional regulations does not affect whether the regional regulations made are legal or not.